Seroprevalence and associated factors of Toxoplasma gondii among HIV-infected patients in Tokyo: A cross sectional study. Issue 1 (January 2020) - Hoshina, Tokio; Horino, Tetsuya; Saiki, Erisha; Aonuma, Hiroka; Sawaki, Kenji; Miyajima, Makiko; Lee, Kwanyole; Nakaharai, Kazuhiko; Shimizu, Akihiro; Hosaka, Yumiko; Kato, Tetsuro; Sato, Fumiya; et al.
Abstract: HIV infection, in particular in patients with developing AIDS, carries a risk of causing toxoplasmosis with encephalitis, which is mostly caused by a form (bradyzoite) of the protozoan parasite Toxoplasma gondii . HIV/AIDS in Japan has been recognized as a serious health issue in recent years. In this study, to elucidate T. gondii seroprevalence in HIV-positive patients in Japan and associated characteristics with Toxoplasma parasite infection, the titer of T. gondii IgG (Tg-IgG) was measured in 399 HIV-positive patients who visited a hospital in Tokyo, Japan, between 2015 and 2017. A questionnaire survey was also conducted to investigate associations between lifestyle and customs. As a result, the overall prevalence of Tg-IgG-positive serum was 8.27% (33 cases of 399). All the cases positive for Tg-IgG were confirmed using the Sabin-Feldman dye test; the titers between each examination correlated robustly ( p < 0.001, r = 0.6). A correlation between Toxoplasma infection rate and age was determined ( p < 0.001), whereas there was no significant correlation with lifestyle customs such as consuming undercooked meat or owning a cat. An association between Toxoplasma infection and experience of dwelling in the Hokkaido area, the northern part of Japan, was observed ( p = 0.001). These results suggested that the proportion of those who were previously exposed to Toxoplasma parasites in the HIV-positive population has been maintained at a similar level as that of the HIV-negative population in Japan, providing clear information about the potential risk of toxoplasmic encephalitis.